Law of contract: a developmental overview - Lilienthal, Gary; Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Masum, Ahmad (CLJ Malaysia Sdn Bhd, 2024)
This chapter gives a cogent legal history of the development of the modern law of contract, from Roman law through to the Puritans’ reconsideration of the law. It explains the role of equity in modern contract law, as well as the developments in the theories of contract, from sin to bargain. Besides, it traces the historical development of the Malaysian legal system briefly with the intention of shedding light on how the law relating to contracts developed in the United Kingdom (UK) was gradually introduced and thereby become part and parcel of the contemporary law of contract in Malaysia. It also explores the situations where English law relating to contracts becomes operational in Malaysia by virtue of the Civil Law Act 1956. Certainly, the reader would benefit from exposure to this essential background narrative when studying the complexity of today’s law of contract.